Analysis of the excess reactivity and control rod worth of RSG-GAS equilibrium silicide core using Continuous-Energy Monte Carlo Serpent2 code. (May 2021) - Sembiring, Tagor Malem; Pinem, Surian; Hartanto, Donny; Liem, Peng Hong
Highlights: A continuation work to confirm the RSG-GAS equilibrium silicide core parameters. Core parameters include excess reactivity and integral & total control rod worth. Experiment results are compared to the results from the Monte Carlo Serpent2 code. Two different nuclear data libraries are used. Abstract: This present work is a continuation of our previous work to verify the RSG-GAS equilibrium silicide core parameters. Earlier, the burnup of 22 fuel elements in the 88th equilibrium core has been measured, and it showed a good agreement between the experimental and calculation results. In this paper, several important neutronics parameters documented from the experiment at the same core, such as the excess reactivity, integral control rod worth, and total control rod worth, are confirmed using the full core calculation results of Monte Carlo Serpent2 code in conjunction with ENDF/B-VII.1 and the most recent ENDF/B-VIII.0 nuclear data libraries. The excess reactivity and integral control rod worth were measured by the positive and negative reactivity compensation method. It is worth mentioning that the measured integral control rod worth hasn't been verified because the in-core fuel management code of RSG-GAS (BATAN-FUEL) solves only for a 2-dimensional configuration. The fuel element burnup at the end of cycle calculated by BATAN-FUEL and Serpent2 is also compared and discussed. The 3-D Serpent2 model of RSG-GAS first core is modified, and several improvements in the models are proposed, including the explicit modeling of 6 neutron beam tubes in the beryllium block reflector. It is found that the calculated integral control rod worth has a good agreement with the experiment, while Serpent2 overestimates the excess reactivity by a maximum of 661 pcm. The impact of nuclear data is insignificant for the selected core parameters.